A new species of Neotorula (Pleosporales) from the Southwest, China - He, Shu-Cheng; Wei, De-Ping; Bhunjun, Chitrabhanu S.; Apurillo, Carlo Chris S.; Thiyagaraja, Vinodhini; Jayawardena, Ruvishika S.; Zhao, Yun-Wei; Zhao, Qi (Phytotaxa, 2024)
A new species, Neotorula nujiangensis, was isolated on dead wood in Nujiang City, Yunnan Province, China. It is characterized by hairy, dark brown colonies with mononematous, straight or flexuous, polytretic conidiophores that comprises a few cells, doliiform or lageniform conidiogenous cells that are acrogenous and chains of multi-septate, verruculose conidia. Phylogenetic analyses of concatenated 28S, 18S, tef1, ITS, and rpb2 sequences showed that this species is closely related to N. aquatica and N. submersa. Neotorula aquatica, N. nujiangensis and N. submersa are in reported Yunnan, China. Neotorula nujiangensis has longer and wider conidia compared to N. aquatica and N. submersa. Neotorula submersa differs from N. aquatica by its thinner conidiophores, longer conidia that are pale yellow when young and tawny to brown when mature, compared to N. aquatica pale green to brown conidia. The combination of morphological observations and molecular data supports establishing this new species.